Neutralizing antibody responses to varicella-zoster virus. - Schmidt, N J (1975)
Neutralization of varicella-zoster (V-Z) virus by human sera and immune rhesus monkey sera was enhanced by fresh guinea pig complement. There was no marked difference in the degree to which complement enhanced neutralization by sera from current V-Z virus infections and sera from long-past varicella infections. Immunoglobulin G neutralizing antibody in sera from varicella cases was enhanced by complement to a slightly higher degree than was immunoglobulin M (IgM) antibody, and immunoglobulin G neutralizing antibody in immune monkey sera was enhanced to a much greater degree than was IgM antibody. There was a rapid decline in the complement requirement of IgM neutralizing antibodies over the course of immunization of the rhesus monkeys. V-Z neutralizing antibody titers in the presence of complement were higher than complement-fixing titers of the same sera in all groups of individuals studied. IgM neutralizing antibody for V-Z virus was demonstrable in all cases of varicella but in only 1 of 22 zoster cases, and V-Z IgM neutralizing antibody was not detectable in primary herpes simplex virus infections in which heterotypic antibody titer rises occurred to V-Z virus. Complement-fixing antibody for V-Z virus was absent in 19S serum fractions which contained IgM neutralizing antibody for the virus.